2020
DOI: 10.21203/rs.3.rs-88788/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Distance Between Sites of Sampling Associated With Genetic Variation Among Neospora Caninum in Aborted Bovine Foetuses From Northern Italy

Abstract: Background: Neospora caninum, a coccidian protozoan, represents an important cause of bovine abortion. While only a single genotype of N. caninum exists word-wide, available N. caninum strains show considerable variation in vitro and in vivo, including different virulence in cattle. To which extent sexual recombination, possible in the intestines of domestic dogs and closely related carnivores as definitive hosts, contribute to this variation is not clear, yet. Methods: Aborted bovine foetuses were collected … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…In Italy, the climatic and environmental factors were determined to influence the N. caninum distribution in cattle by geographical information system (GIS) and remote sensing (RS) technology (58). Additionally, Villa et al (62) found a correlation between the geographic distance of the sampling sites and genetic distance of N. caninum, further explaining the possible reasons for the seroprevalence difference among different regions. In our investigation, no statistically significant difference in N. caninum seroprevalence was observed between black goats of different genders (P = 0.083).…”
Section: Discussionmentioning
confidence: 98%
“…In Italy, the climatic and environmental factors were determined to influence the N. caninum distribution in cattle by geographical information system (GIS) and remote sensing (RS) technology (58). Additionally, Villa et al (62) found a correlation between the geographic distance of the sampling sites and genetic distance of N. caninum, further explaining the possible reasons for the seroprevalence difference among different regions. In our investigation, no statistically significant difference in N. caninum seroprevalence was observed between black goats of different genders (P = 0.083).…”
Section: Discussionmentioning
confidence: 98%